2014
DOI: 10.1371/journal.pone.0111837
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution and Expansion Analysis of the NAC Transcription Factor in Zea mays

Abstract: NAC (NAM, ATAF1, 2 and CUC2) family is a plant-specific transcription factor and it controls various plant developmental processes. In the current study, 124 NAC members were identified in Zea mays and were phylogenetically clustered into 13 distinct subfamilies. The whole genome duplication (WGD), especially an additional WGD event, may lead to expanding ZmNAC members. Different subfamily has different expansion rate, and NAC subfamily preference was found during the expansion in maize. Moreover, the duplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 70 publications
0
50
0
Order By: Relevance
“…S2b). The gene retentions and losses might be associated with the related functions during plant evolution29.…”
Section: Discussionmentioning
confidence: 99%
“…S2b). The gene retentions and losses might be associated with the related functions during plant evolution29.…”
Section: Discussionmentioning
confidence: 99%
“…These numbers are relatively similar to those previously reported in these species. Previously, 105 (Ooka et al, 2003) and 117 (Nuruzzaman et al, 2010) NAC genes were identified in Arabidopsis, 288 (Pereira-Santana et al, 2015) and 163 (Hu et al, 2010) in poplar, 189 in eucalyptus (Hussey et al, 2015), 97 in barrel medic (Ling et al, 2017), 124 (Fan et al, 2014) and 152 (Shiriga et al, 2014) in maize, 147 in foxtail millet (Puranik et al, 2013), 151 (Nuruzzaman et al, 2010) and 140 (Fang et al, 2008) in rice, 107 (You et al, 2015) and 118 (Zhu et al, 2015) in brome and 131 (Sanjari et al, 2019) and 145 (Kadier et al, 2017) in sorghum.…”
Section: Phylogenetic Analyses Of the Nac Transcription Factor Familymentioning
confidence: 99%
“…The first reported NAP member was a target gene of AP3/PI in Arabidopsis thaliana (Sablowski and Meyerowitz 1998). As a plantspecific transcription factor, NAP proteins have been identified in various plant species, including rice (Jeong et al 2010), bamboo (Chen et al 2011b), wheat (Uauy et al 2006), cotton (Meng et al 2009), grape (Fernandez et al 2006), maize (Fan et al 2014), and soybean (Meng et al 2007).…”
Section: Introductionmentioning
confidence: 99%